Development of a new purified vero cell rabies vaccine (Rabivax-S) at the serum institute of India Pvt Ltd - Prasad S. Kulkarni; Ashish Sahai; Bhagwat Gunale; Rajeev M Dhere (Taylor & Francis Group, 2017)
Introduction: Rabies is a 100% fatal disease with significant disease burden in Asia and Africa but preventable with vaccines and immunoglobulins. There are very few WHO prequalified cell culture derived rabies vaccines available globally for use in humans. We have developed a new purified vero cell rabies vaccine (Rabivax-S) to meet this demand. Areas covered: In this review, we have described the detailed manufacturing process of Rabivax-S and summary of preclinical and clinical development based on the data generated in-house. Expert commentary: Rabivax-S has been developed on Vero ATCC CCL81 cells using Pitman Moore (PM3218) strain. Following all the GMP requirements the vaccine was tested in GLP toxicology studies. Further it underwent clinical trials in preexposure and postexposure settings and was found safe and immunogenic.